A Facile Synthesis of Robinson's NHC‐Stabilised Diborane(4). Issue 40 (23rd July 2020) - Trose, Michael; Cordes, David B.; Slawin, Alexandra M. Z.; Stasch, Andreas
Abstract : Reactions of bis(pinacolato)diboron (B2 pin2 ) with [(IDip)AlH3 ] {IDip = (HCNDip)2 C:, Dip = 2, 6‐ i Pr2 C6 H3 } afforded both the new diborane [(IDip)BH2 B(pin)] and the known compound [(IDip)BH2 BH2 (IDip)] in a facile one‐pot procedure; the latter reaction is improved by the addition of free IDip. [(IDip)AlH3 ] transfers both IDip and hydride ligands to the diborane moiety in a halide‐free approach. [(IDip)BH2 B(pin)] was structurally and spectroscopically characterised and additional spectroscopic data for [(IDip)BH2 BH2 (IDip)] is reported. Abstract : Bis(pinacolato)diboron reacts with the NHC aluminium hydride [(IDip)AlH3 ] in a one‐step protocol to [(IDip)BH2 B(pin)] and [(IDip)BH2 BH2 (IDip)]. [(IDip)AlH3 ] transfers both hydride and NHC ligands to the diborane moiety in a halide‐free approach and the ligand exchange process to the diborane(4) complex is enabled by the addition of free NHC ligand.